Characterization of chickpea (Cicer arietinum L.) lectin for biological activity - Gautam, Ajay Kumar; Gupta, Neha; Narvekar, Dakshita T.; Bhadkariya, Rajni; Bhagyawant, Sameer S. (Physiology and molecular biology of plants, 2018)
Lectins are proteins that are subject of intense investigations. Information on lectin from chickpea ( Cicer arietinum L.) with respect to its biological activities are very limited. In this study, we purified lectin from the seeds of chickpea employing DEAE-cellulose and SP-Sephadex ion exchange chromatography and identified its molecular subunit mass as 35 kDa. The free radical scavenging activity of lectin measured by the DPPH assay has IC 50 of 0.88 µg/mL. Lectin exerted antifungal activity against Candida krusei , Fusarium oxysporium oxysporium , Saccharomyces cerevisiae and Candida albicans , while antibacterial activity against E. coli , B. subtilis , S. marcescens and P. aeruginosa. The minimum inhibitory concentrations were 200, 240, 160 and 140 µg for C. krusei, F. oxysporium , S. cerevisiae and C. albicans respectively. Lectin was further examined for its antiproliferative potential against cancerous cell line. The cell viability assay indicated a high inhibition activity on Ishikawa, HepG2, MCF-7 and MDA-MB-231 with IC 50 value of 46.67, 44.20, 53.58 and 37.46 µg/mL respectively. These results can provide a background for future research into the benefits of chickpea lectin to pharmacological perspective.